Essential Oil Composition and Antimicrobial Activities of Two Closely Related Species, Alpinia mutica Roxb. and Alpinia latilabris Ridl., from Peninsular Malaysia. (27th May 2014) - Ibrahim, Halijah; Sivasothy, Yasodha; Syamsir, Devi Rosmy; Nagoor, Noor Hasima; Jamil, Natasha; Awang, Khalijah
Abstract : The essential oils obtained by hydrodistillation of the unripe and ripe fruits of Alpinia mutica Roxb. and Alpinia latilabris Ridl. were analysed by capillary GC and GC-MS. The oils were principally monoterpenic in nature. The unripe and ripe fruit oils of A. mutica were characterized by camphor (21.0% and 15.8%), camphene (16.6% and 10.2%), β -pinene (8.6% and 13.5%), and trans, trans -farnesol (8.0% and 11.2%), respectively. The oils of the unripe and ripe fruits were moderately active against Staphylococcus aureus, Bacillus subtilis, Trichophyton mentagrophytes, and Trichophyton rubrum . 1, 8-Cineole (34.2% and 35.9%) and β -pinene (20.2% and 19.0%) were the two most abundant components in the unripe and ripe fruit oils of A. latilabris . The oil of the unripe fruits elicits moderate activity against Staphylococcus aureus and Trichophyton mentagrophytes while Candida glabrata was moderately sensitive to the oil of the ripe fruits.